Analisis Pelanggaran Hak Pada Manusia Dalam Kasus Pembunuhan Laskar FPI Di Km.50 - Faturohman Faturohman; Naman Naman; Saripan Saripan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This murder case involving Laskar members is an incident that has a significant impact on the rights of every human being. This violation of human rights resulted in the deaths of six members. Law enforcement in this case has attracted various controversies, especially regarding the use of force which was allegedly excessive or disproportionate. Every individual, including members of this organization, has the right to be protected from physical violence or threats of death. One of the principles of the rights that every human being has is that it is necessary to carry out an independent and transparent investigation into every alleged violation of human rights, this includes cases of murder of irregulars. The implementation of the rights of every human being can also include various aspects of accountability for the officers involved in this case, namely that they must be responsible for their actions in accordance with applicable regulations, and also a judicial process that is carried out as fairly as possible.